Improve Vocabulary by Using Media Animated the Folklore of Malin Kundang - Ahmad Sofwan Sabily; Suryadi Suryadi (Institut Agama Islam Negeri Palopo, 2022)
In addition to local expertise that we must conserve, such as folklore, the rapid growth of technology in the field of education makes learning easier through tools like audio-visual animation media. Malin Kundang is just one example of the many varieties of folklore that exist. The goals of this research are threefold: (1) to determine whether or not students can benefit from learning about Malin Kundang folklore; (2) to use Malin Kundang folklore as a means to expand vocabulary; and (3) to determine whether or not using Malin Kundang folklore can be used to improve learning outcomes. In this work, we employ quantitative techniques. In order to describe events, establish links, or test hypotheses, quantitative research relies on the collection and analysis of numerical data. A student survey is one example of such a device. The researcher employed SPPS to perform the necessary calculations. Students' comprehension of the English language is significantly improved when they are exposed to animated media based on malin kundang folklore, according to a review of the available research.